Guillain-Barré-like axonal polyneuropathy associated with Toscana virus infection: A case report. Issue 38 (September 2017) - Rota, Eugenia; Morelli, Nicola; Immovilli, Paolo; De Mitri, Paola; Guidetti, Donata
Abstract: Rationale: Numerous cases of post-infectious Guillain-Barré syndrome (GBS) have been reported in the literature. Toscana virus (TOSV) is an arthropod-borne emerging pathogen in the Mediterranean area. Patient concerns: A 40-year-old male patient was admitted to hospital for acute facial weakness, associated to numbness paraesthesias at lower and upper limbs. The neurological examination revealed facial diplegia and reduced tendon reflexes. The nerve conduction studies documented an acute motor and sensory axonal neuropathy (AMSAN); the lumbar puncture detected albuminocytologic dissociation. Serology for human immunodeficiency virus (HIV), Epstein-Barr Virus (EBV), Cytomegalovirus (CMV), mumps, and Borrelia was negative, as was cerebrospinal fluid (CSF) polymerase chain reaction assay for Herpes virus, Borrelia, Mycoplasma pneumoniae, Cryptococcus, and Mycobacterium tubercolosis. Positivity for TOSV IgG antibodies was found on both CSF and serum; the patient remembered being recently exposed to mosquitoes. Diagnoses: The AMSAN subtype of GBS, subsequent to a TOSV infection, was diagnosed. Interventions: The patient was treated with plasma-exchange with complete clinical recovery, but a relapse occurred 9 months later, when the nerve conduction studies confirmed the presence of an AMSAN, which benefited from oral steroids. Outcomes: A good clinical recovery was achieved after treatments. Lessons: This is the first case, to the best of our knowledge, of a TOSV infection associated to a peripheral neuropathy mimicking a GBS syndrome, both clinically and electrophysiologically. The clinical spectrum of TOSV neurological complications seems to be wider than previously known: this should be taken into account by the scientific community and public health institutions.